Polyphenols and Antioxidant Activity of Thunbergia laurifolia Infused Tea under Drying Conditions - Justice A. Essiedu; Hellie Gonu; Parise Adadi; Ulaiwan Withayagiat (Journal of Food Quality)
Thunbergia laurifolia leaf is used in Thai herbal medicine to moderate alcohol, food poisoning, and other health-related diseases mainly due to its overwhelming phytochemical compounds which exert several biological functions such as antioxidant, and anti-inflammatory properties, among others. This study investigated the potential effects of hot air-drying conditions (TL-D80°C, TL-D90°C, and TL -D100°C) of T. laurifolia tea leaves on phenolic compounds, total flavonoid content (TFC), total phenolic content (TPC), and antioxidant activities (AOA) of the infused teas. The results show that an increase in drying temperature significantly p<0.05 improved TPC (709.7 ± 1.36–744.8 ± 5.79 mg GAE/) and TFC (198.98 ± 7.59–207.16 ± 4.10 mg RE/L) of infused teas. TL-D80°C (69.9 ± 0.95%) and TL-D90°C (69.3 ± 0.7%) infused teas showed significantly p<0.05 higher DPPH inhibitory effect compared to TL-D100°C. Treatment had no effects p>0.05 on ABTS.+ scavenging activity. The phenolic compounds detected in infused teas were rosmarinic acid, caffeic acid, gallic acid, catechin, rutin, and quercetin. Regarding, the cumulative phenolic compounds TL-D100°C infused teas were significantly higher p<0.05 compared to TL-D90°C and TL-D80°C. The results suggest that drying conditions (i.e., TL-D100°C within 30 min) could be used to achieve appropriate moisture content of T. laurifolia tea leaves without compromising the phytochemical compositions and antioxidant potentials of the resulting infused teas.